Immunohistochemical expression of Galectin-3 in canine tumors - Vargas, Thiago H. M.; Pulz, Lidia H.; Strefezzi, Ricardo F. (Brazilian Journal of Veterinary Pathology, 2018)
Galectin-3 (Gal-3) is a protein expressed by both normal and neoplastic cells. It participates in several biological processes such as cell proliferation, cell adhesion, apoptosis, tissue remodeling, and angiogenesis. Although it is known to serve as a valuable prognostic marker in several types of human cancer, there are few reports about its applicability as a marker in the veterinary oncology literature. The aim of the present study was to characterize Gal-3 expression in different types of canine tumors. Fifty-three tissue samples from 22 histologically different types of canine tumors were immunohistochemically evaluated for Gal-3 expression. Variations in the percentage of Gal-3-positive cells, localization of Gal-3 protein, and percentage of Gal-3-positive fibroblasts were observed. These preliminary results showed variable expression of Gal-3 among canine tumors. Further studies are needed in order to investigate the potential of this protein as a prognostic marker and a therapeutic target.